Magnetic Resonance Imaging Appearance of Giant Intracerebral Tuberculoma: A Retrospective Analysis - Boruah, Deb; Sarma, Kalyan; Gogoi , Pallavi; Singh, Binoy; Gogoi, Bidyut; Hazarika, Karuna; Sharma , Barun; Phukan, Pranjal (Acta medica Lituanica, 2022)
Background: Giant intracerebral tuberculomas are rare lesions but should be considered in the differential diagnosis of intracranial space-occupying lesion in an endemic region.Objective: The purpose of this study is to analyze the clinical data and magnetic resonance imaging (MRI) findings of giant intracerebral tuberculomas to improve the diagnostic precision.Material and Methods: The clinical and MRI findings of 22 patients of giant intracerebral tuberculoma were analyzed retrospectively. For the statistical analysis independent sample Student t-test was used.Results: For 22 patients included in this sample the giant intracerebral tuberculoma was of size more than 2.5cm. The majority of the giant tuberculomas (19 patients (86.4%))was located in the supratentorial area.T2-weighted hypointense core of giant tuberculoma was observed in 12 patients (54.5%) and T1 hyperintensities were observed in peripheral (wall) of the giant tuberculoma in 14 patients (63.6%). The mean ADC value of the peripheral (wall) of the giant tuberculoma was 1.034± 0.466[SD] x 10-3mm2/s and the core was 0.994± 0.455[SD] x 10-3mm2/s with a statistically significant difference (p-value
Keywords: Tuberculosis (TB); giant tuberculoma; Diffusion-weighted imaging (DWI); MR spectroscopy